The sergeant's matchmaking dog - Nichols, Carrie (Nichols, Carrie. Small-town sweethearts., 2021)
Former marine Gabe Bishop is focused on readjusting to civilian life. So the last thing he needs is the adorable kid next door bonding with his dog, Radar--and the boy's guardian butting in. Addie Miller is afraid of dogs, so why does she keep coming around and making his heart melt? Soon, Gabe finds himself teaching Addie about the beauty of the human-canine bond...and becoming her shoulder to lean on. Could his new neighbors be everything Gabe never knew he needed?